Effect of eight-week intervention programme on the knowledge, attitude and utilization of eye protective devices among welders in Ibadan North Local Government Area of Oyo State, Nigeria (2013)
The purpose of this study was to investigate the effects of eight-week intervention programme on knowledge, attitude and utilization of eye protective devices among welders in lbadan, Oyo State, Nigeria. The study sample consisted of 50 welders (test group) at Bodija-Ojurin area and 50 welders (control group) at Agodi-Gate area both in lbadan North Local Government Area. Knowledge, attitude and utilization of eye protective devices questionnaire was the major instrument employed to gather information. Data collected were analysed using inferential statistics of ANOVA. The post test result showed that the knowledge and attitude in the experimental group after the intervention programme increased significantly but utilization of eye protective devices remained static.